Can we read letters? : reflections on fundamental issues in reading and dyslexia research - Tønnessen, Finn Egil; Uppstad, Per Henning (SensePublishers, 2015)
ĹℓIn their new book, Finn Egil T©ınnessen and Per Henning Uppstad provide a set of theoretical and philosophical reflections on research in reading and dyslexia. It is a pleasure to welcome this book, which reflects the many contributions made by researchers at the National Centre for Reading Education and Research in Stavanger, Norway. Professor Usha Goswami, University of Cambridge. Careful reflection on the concepts and methods used is a prerequisite for further development in any field of research. The authors think cognitive psychology has become too dominant in reading and dyslexia research, arguing that it should be combined with behaviourism and connectionism in part by focusing on the concept of skill. The key components of a skill are claimed to be automaticity, awareness and shifts between them. Reading is defined as an interpretative skill, which should be viewed from the perspective of hermeneutics. The authors use these fundamental analyses and definitions to shed new light on the balanced approach to reading instruction, reading fluency and other key concepts. The book also deals with problems in the definition of dyslexia and proposes a method to arrive at clear and fruitful definitions. It concludes with a chapter trying to answer the question of in what sense, or to what extent, it can be claimed that reading and dyslexia research has made progress. The book mainly builds on articles published over the past 25 years by Professor Finn Egil T©ınnessen at the National Centre for Reading Education and Research, Stavanger, Norway.